2022
DOI: 10.1093/jas/skac028.078
|View full text |Cite
|
Sign up to set email alerts
|

86 Evaluation of the Super Smartfeeder System (C-Lock, Inc) for Lamb Supplemental Feeding in a Pasture-based System

Abstract: The C-Lock, Inc Super SmartFeeder (feeder) may provide opportunities to evaluate lamb supplemental feeding behavior on pasture. The objective of this study was to determine lamb feeding capacity, lamb feeding behavior, and methodologies for training lambs to this feeding system. Post-weaning, lambs (n = 179) were introduced to the feeder (day 0) on fescue-based pasture at the Southwest Virginia Agricultural Research and Extension Center. For 24 days, lambs were supplemented 0.23 kg/hd/day with the feeder on pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…From d 6 to d 24, 72% of lambs visited the SSF daily. The success rate of post-weaning lambs reported by Valliere et al [ 12 ] is greater than that observed in weaned steers in Experiment 2. Both the current studies and the study reported by Valliere et al [ 12 ] suggest longer acclimation periods may prove helpful in improving the utilization of precision feeding technologies.…”
Section: Resultscontrasting
confidence: 56%
See 2 more Smart Citations
“…From d 6 to d 24, 72% of lambs visited the SSF daily. The success rate of post-weaning lambs reported by Valliere et al [ 12 ] is greater than that observed in weaned steers in Experiment 2. Both the current studies and the study reported by Valliere et al [ 12 ] suggest longer acclimation periods may prove helpful in improving the utilization of precision feeding technologies.…”
Section: Resultscontrasting
confidence: 56%
“…Similar to the weaned steer study, a study by Valliere et al [ 12 ] reported a 24 d acclimation period for post-weaning lambs (n = 179) on pasture. Lambs were offered 0.23 kg of supplement daily from an SSF in a pasture setting.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation